New narratives of disability : constructions, clashes, and controversies - Green, Sara E.; Loseke, Donileen R. (Emerald Publishing Limited, 2019)
This volume explores questions about narrative frameworks in disability research. Narrative is a omnipresent meaning-producing communication form in social life that is both cultural and personal. Public understandings of disability tend to follow a medical storyline in which disability is a personal tragedy to be treated through professional intervention - a frame that disempowers and fails to resonate with many disabled people. Scholars in disability studies and the social sciences have proposed an alternative that portrays social structures, forces, and attitudes as the problems to be resolved - a frame that, while empowering, may neglect, or even repress, some kinds of personal disability stories. This volume seeks to answer the call for richer, more diverse understandings of disability. We explore how narrative inquiry can broaden perspectives on disability to include pain, suffering, chronic illness, and episodic disability, as well as the perspectives of family members and caregivers, while also serving as a platform for dismantling prejudice and discrimination in order to promote positive social change.
Includes index.
Keywords: People with disabilities -- Social life and customs.; People with disabilities -- Research.; Social Science, People with Disabilities.; Disability: social aspects.; elektronické knihy; electronic books